Thermoresponsive interfaces obtained using poly(N-isopropylacrylamide)-based copolymer for bioseparation and tissue engineering applications - Nagase, Kenichi (Advances in colloid and interface science, 2021)
Poly(N-isopropylacrylamide) (PNIPAAm) is the most well-known and widely used stimuli-responsive polymer in the biomedical field owing to its ability to undergo temperature-dependent hydration and dehydration with temperature variations, causing hydrophilic and hydrophobic alterations. This temperature-dependent property of PNIPAAm provides functionality to interfaces containing PNIPAAm. Notably, the hydrophilic and hydrophobic alterations caused by the change in the temperature-responsive property of PNIPAAm-modified interfaces induce temperature-modulated interactions with biomolecules, proteins, and cells. This intrinsic property of PNIPAAm can be effectively used in various biomedical applications, particularly in bioseparation and tissue engineering applications, owing to the functionality of PNIPAAm-modified interfaces based on the temperature modulation of the interaction between PNIPAAm-modified interfaces and biomolecules and cells. This review focuses on PNIPAAm-modified interfaces in terms of preparation method, properties, and their applications. Advances in PNIPAAm-modified interfaces for existing and developing applications are also summarized. [Display omitted] •PNIPAAm-modified interfaces exhibit a thermoresponsive property change.•These interfaces can separate biopharmaceutics and cells with their activity.•The interfaces can fabricate functional cellular tissue for tissue engineering.•PNIPAAm-modified interfaces can also be used in future biomedical applications.